The Use of Peer Teaching in the Online Clinical PBL: The Medical Students’ Perspectives - Romão GS; Rocha SR; Faria Junior M; Durand MT; Bestetti RB (Advances in Medical Education and Practice)
Gustavo Salata Romão,1 Sheyla Ribeiro Rocha,2 Milton Faria Junior,1 Marina de Toledo Durand,1 Reinaldo Bulgarelli Bestetti1 1Medical Course, University of Ribeirão Preto, Ribeirão Preto, São Paulo, Brazil; 2Department of Medicine, Federal University of São Carlos, São Carlos, São Paulo, BrazilCorrespondence: Gustavo Salata Romão; Reinaldo Bulgarelli Bestetti, Email gsalata@uol.com.br; rbestetti44@gmail.comPurpose: To evaluate medical students’ perceptions about using peer teaching (PT) in the online Clinical PBL (C-PBL).Materials and Methods: The C-PBL used in the Primary care Unit (PCU) of the medical course of the Ribeirao Preto University was adapted to the virtual environment. A PT session was included to enhance students’ intrinsic motivation. This cross-sectional study applied a 14-item survey to evaluate the perceptions of 378 medical students from the first to the seventh semester about the use of PT in this context.Results: According to participants’ perceptions, the use of PT in the online C-PBL allowed the interactive participation of students and produced satisfactory knowledge acquisition. Preparing and presenting a slideshow and being taught by peers contributed significantly to their learning. The survey used to collect information presented a high internal consistency measured by Cronbach’s alpha.Conclusion: From the students’ perspectives, the use of PT in the online C-PBL was satisfactory and improved learning for peer teachers and learners. This study contributes additional evidence suggesting that PT is an effective teaching strategy in online learning and can be associated with PBL. This finding has implications for curriculum development and the health system.Keywords: peer teaching, clinical PBL, problem based learning, virtual learning, educational technology